Information exchange networks for chronic diseases in primary care practices in Germany: a cross-sectional study - Arnold, Christine; Hennrich, Patrick; Wensing, Michel (BMC primary care, 2022)
Coordination of care requires information exchange between health workers. The structure of their information exchange networks may influence the quality and efficiency of healthcare delivery. The aim of this study was to explore and classify information exchange networks in primary care for patients with chronic diseases in Germany.
Gesehen am 30.03.2022